Hexaphosphapentaprismane: A New Gateway to Organophosphorus Cage Compound Chemistry - Zenneck, Ulrich; Al-Ktaifani,; Bauer, Walter; Bergsträßer, U.; Breit, B.; Francis, M. D.; Heinemann, Frank Wilhelm; Hitchcock, P. B.; Mack, A.; Nixon, J. F.; Pritzkow, Hans; Regitz, M.; et al. (Chemistry - A European Journal, 2002)
Several independent synthetic routes are described leading to the formation of a novel unsaturated tetracyclic phosphorus carbon cage compound tBu4C4P6 (1), which undergoes a light-induced valence isomerization to produce the first hexaphosphapentaprismane cage tBu4C4P6 (2). A second unsaturated isomer tBu4C4P6 (9) of 1 and the bis-[W(CO)5] complex 13 of 1 are stable towards similar isomerization reactions. Another starting material for the synthesis of the hexaphosphapentaprismane cage tBu4C4P6 (2) is the trimeric mercury complex [(tBu4C4P6)Hg]3 (11), which undergoes elimination of mercury to afford the title compound 2. Single-crystal X-ray structural determinations have been carried out on compounds 1, 2, 9, 11, and 13.
UnivIS-Import:2017-11-07:Pub.2002.nat.dchph.paoc22.hexaph
Keywords: Cage compounds; Heterocycles; Pentaprismanes; Phosphorus; Strained molecules